2020
DOI: 10.1002/iub.2247
|View full text |Cite
|
Sign up to set email alerts
|

The sodium channel NaX: Possible player in excitation–contraction coupling

Abstract: The sodium channel NaX (encoded by the SCN7A gene) was originally identified in the heart and skeletal muscle and is structurally similar to the other voltage‐gated sodium channels but does not appear to be voltage gated. Although NaX is expressed at high levels in cardiac and skeletal muscle, little information exists on the function of NaX in these tissues. Transcriptional profiling of ion channels in the heart in a subset of patients with Brugada syndrome revealed an inverse relationship between the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, atrial and ventricular arrhythmias can also be induced by caffeine, which is able to interfere with calcium homeostasis [ 115 , 119 ] by increasing intracellular calcium concentration [ 115 ]. Indeed, it was demonstrated that caffeine is able to stimulate calcium release from the sarcoplasmic reticulum [ 120 ], and calcium imbalances, particularly sarcoplasmic reticulum calcium stores, may be altered in BrS [ 121 , 122 , 123 ]. A 24-year-old male developed arrhythmias and collapsed after the ingestion, for the first time, of a small quantity of an energy drink combined with alcohol; specifically, the drink contained 80 mg of caffeine and 1000 mg of taurine, plus Vodka.…”
Section: Arrhythmogenic Ingredientsmentioning
confidence: 99%
“…Furthermore, atrial and ventricular arrhythmias can also be induced by caffeine, which is able to interfere with calcium homeostasis [ 115 , 119 ] by increasing intracellular calcium concentration [ 115 ]. Indeed, it was demonstrated that caffeine is able to stimulate calcium release from the sarcoplasmic reticulum [ 120 ], and calcium imbalances, particularly sarcoplasmic reticulum calcium stores, may be altered in BrS [ 121 , 122 , 123 ]. A 24-year-old male developed arrhythmias and collapsed after the ingestion, for the first time, of a small quantity of an energy drink combined with alcohol; specifically, the drink contained 80 mg of caffeine and 1000 mg of taurine, plus Vodka.…”
Section: Arrhythmogenic Ingredientsmentioning
confidence: 99%
“…Sarbjit-Singh et al [ 24 ] found that caffeine may inactivate the Nav1.4 channel in murine skeletal muscle fibers, leading to sodium current inhibition. Moreover, levels of the Nav1.5 and NaX proteins were downregulated by caffeine, changes that were associated with increased intracellular calcium concentrations in cardiac myocytes [ 25 ]. On the other hand, the main transducer in thermal (heat) pain sensory neurons is transient receptor potential cation channel subfamily V member 1 (TRPV1), where temperature gradually increases its activity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%